2011
DOI: 10.5489/cuaj.10201
|View full text |Cite
|
Sign up to set email alerts
|

A feasibility trial of a cognitive-behavioural symptom management program for chronic pelvic pain for men with refractory chronic prostatitis/chronic pelvic pain syndrome

Abstract: The psychosocial management program targets and significantly reduces several empirically supported psychosocial risk factors associated with poorer CP/CPPS outcomes. Psychosocial management for CP/CPPS is feasible, but requires a randomized controlled trial with longitudinal follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 28 publications
(19 reference statements)
0
20
0
Order By: Relevance
“…6,8,9 It has been suggested that psychologically based treatments can be effective in the management of CPP in addition to medical and surgical management. 10,11 Moreover, there has been recent publication in support of multidisciplinary CPP services, including a male CPP PMP: the LINK PMP. 12 In the context of the evidence of heightened levels of psychological distress and painrelated disabilities, a clear rationale can be seen for the provision of a PMP designed to support and promote self-management strategies within this pain population.…”
Section: Introductionmentioning
confidence: 99%
“…6,8,9 It has been suggested that psychologically based treatments can be effective in the management of CPP in addition to medical and surgical management. 10,11 Moreover, there has been recent publication in support of multidisciplinary CPP services, including a male CPP PMP: the LINK PMP. 12 In the context of the evidence of heightened levels of psychological distress and painrelated disabilities, a clear rationale can be seen for the provision of a PMP designed to support and promote self-management strategies within this pain population.…”
Section: Introductionmentioning
confidence: 99%
“…27 This previously-identified style of negative CP/CPPS processing 5,7,10,12,14 can be modified, and reductions in catastrophizing have been shown to be associated with reductions in CP/CPPS symptoms. 28 This study also strongly indicated that illness-focused coping is an important target in improving patients' mental and physical QoL. Previous research has examined the use of pain-contingent rest as a coping strategy in men with CP/ CPPS, and found that it predicted disability 12 and poorer physical QoL.…”
Section: Discussionmentioning
confidence: 86%
“…To improve mental QoL, catastrophizing should be reduced. Interventions have been successful in reducing catastrophizing in CP/CPPS 28 by teaching patients how to identify and modify catastrophic interpretations of symptom-associated life events, and by promoting renewed social and physical activity engagement. Moreover, physicians can address patients' catastrophizing in their offices using various strategies (e.g., increasing patient self-awareness, suggesting readings for self-management).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, longitudinal research suggests that if patients with IBD develop good coping mechanisms early in their disease, they are less likely to report poorer mood that can exacerbate symptoms later on (Lix et al, 2008). Psychological treatment does benefit disease and symptom management as shown in recent abdominal-pelvic pain research (Boye et al, 2011;Tripp, Nickel, & Katz, 2011). Tripp et al (2011) used a cognitive-behavioural therapy framework aimed at improving QoL in men with chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS).…”
Section: Discussionmentioning
confidence: 98%